Family Counseling Anticipating Bullying Behavior In Children - Azmatul Khairiah Sari, Neviyarni S, Yarmis Syukur (Journal of Education and Teaching Learning, 2021)
Family counseling is an important thing for a counselor to do. Many benefits will be obtained by a counselor from providing family counseling. Family counseling which is the provision of services in the form of a system will also touch the client to the child. The rise of bullying cases that occur in children causes counselors and parents to anticipate in advance so that children do not become perpetrators or victims of bullying behavior. From bullying behavior, children who become victims will become low self-esteem, isolate themselves from social and many other negative impacts that can be caused. Therefore, family counseling is one of the solutions to prevent bullying from happening to children